Penyelesaian Sengketa Alternatif Dalam Perselisihan Perdata: Suatu Rekomendasi Pembaharuan Hukum Formal Yang Responsif - Aries Isnandar (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2004)
This study aims to explore the effectiveness of alternative dispute resolution (ADR) in handling civil disputes and formulating recommendations for formal legal reform that is more responsive to the needs of the community. The research method used is normative juridical with a legislative approach and conceptual analysis. Data was obtained through a literature study that included legislation, court decisions, and related literature. The results of the study show that ADR mechanisms, such as mediation and arbitration, have great potential to resolve disputes more quickly, efficiently, and fairly than litigation. However, limitations in regulation and implementation are still obstacles. Therefore, more adaptive formal legal reforms are needed, including enhancing the role of judges in promoting ADR and harmonizing procedural rules to strengthen its effectiveness in the Indonesian legal system.